A spatial assessment of livestock production and market access - Tilahun, Helina; Schmidt, Emily (International Food Policy Research Institute, 2013)
This study links smallholder livestock production data from the Agricultural Census (2001/02) and annual CSA agricultural sample survey with Geographic Information Systems (GIS) data on land cover, city population, and road networks in order to assess the relationship between livestock population, market access, and grazing land. We use existing studies of travel time to calculate shares of livestock populations within defined travel time thresholds of major markets. In addition, we attempt to provide greater insight into changes in available grazing land given Ethiopia’s increasing human and livestock population pressure.